Respuesta :

  • y=x+2.....(1)
  • y+1= – 4x......(2)

Put value of y in Equation 1 in Equation 2.

[tex] \looparrowright \sf y + 1 = - 4x[/tex]

[tex] \\ \\ [/tex]

[tex] \looparrowright \sf (x + 2) + 1 = - 4x[/tex]

[tex] \\ \\ [/tex]

[tex] \looparrowright \sf x + 2 + 1 = - 4x[/tex]

[tex] \\ \\ [/tex]

[tex] \looparrowright \sf x +3= - 4x[/tex]

[tex] \\ \\ [/tex]

[tex] \looparrowright \sf x + 4x= - 3[/tex]

[tex] \\ \\ [/tex]

[tex]\looparrowright \sf 5x= - 3[/tex]

[tex] \\ \\ [/tex]

[tex]\looparrowright \sf x= \dfrac{ - 3}{5} [/tex]

[tex] \\ \\ [/tex]

Let's find value of y :

[tex] \\ \\ [/tex]

[tex]\looparrowright \sf y=x+2[/tex]

[tex] \\ \\ [/tex]

[tex]\looparrowright \sf y= \dfrac{ - 3}{5} +2[/tex]

[tex] \\ \\ [/tex]

[tex]\looparrowright \sf y= \dfrac{ - 3 + 10}{5} [/tex]

[tex] \\ \\ [/tex]

[tex]\looparrowright \sf y= \dfrac{7}{5} [/tex]

Solution:

[tex]\looparrowright \sf \bigg( \dfrac{ - 3}{5} , \dfrac{7}{5} \bigg)[/tex]